Faktor-Faktor Yang Berhubungan Dengan Kepatuhan Perawat Dalam Melaksanakan Standar Prosedur Operasional Pelayanan Klinik di Instalasi Rawat Jalan Rumah Sakit Umum Kabupaten Tangerang Tahun 2018 - Happy Novriyanti Purwadi; Resna A. Soerawidjaja; Yunita Anggraeni (APIKES Bhumi Husada Jakarta, 2018)
ABSTRACT Introduction Compliance is part of the individual's behavior to obey something, so the nurse's compliance in implementing the standard operational procedure (SPO). There are several factors related to the compliance of nurses in implementing SPO among others age, length of work, education, gender, and employment status, the reward system, rewards, availability of facilities and infrastructure, and training. The research method is cross-sectional by observation and fill out the questionnaire using total sampling with the amount of 42 respondents. Result of the obedient 76.2% compliance of nurses compliance, while 23.8% were noncompliant. Ratio prevalence factors characteristic age of age comparison ≥30 years : age <30 years = 1: 1. Comparison of working length >5 years with a working period ≤5 years = 1: 1. Comparison of education, further education: initial education = 1: 1. Comparison of sex, male : female = 1: 1. Comparison of employment status, civil servant: non-civil = 1: 2. The factor of reward system, reward, availability of facilities and infrastructure, proved no significant relation with nursing nurses. Value of Pvalue> value of α= 0,05. The conclusion that there is no relationship to nurse compliance. Suggestion, it is expected that the nurse can increase the awareness and nurse in the compliance of the nurse in implementing the SPO. Keywords: nurse compliance, standard operational procedures